Effects of reproductive technologies and SPF status on some physiological and behavioral characteristics in rats with arterial hypertension (ISIAH strain) - D. S. Ragaeva; T. O. Abramova; I. N. Rozhkova; E. Yu. Brusentsev; E. V. Kalinichenko; T. N. Igonina; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
Modern standards of Laboratory Animal Science include working with laboratory animals of high quality, in particular, with specific pathogen free (SPF) mice and rats. On the other hand, assisted reproductive technologies (ART) are widely used in modern medicine for human infertility treatment as well as for genome resource banking. In the present study, a comparison of body weight, blood pressure (BP) and behavior in the «elevated plus maze» (EPM) test was made between three groups of ISIAH (inherited stress induced arterial hypertension) rats: a group of animals that were born and raised in a conventional animal facility and two groups from an SPF animal facility (one with animals born naturally and another with animals resulting from ART). There were no changes in BP between the groups, but the behavior of ISIAH differed depending on rearing conditions. In particular, grooming time, as well as the number of defecations and the number of urinations during the test were decreased in both groups of ISIAH rats born in the SPF animal facility as compared to ISIAH rats born in the conventional animal facility. The behavior of the ISIAH rat offspring resulting from ART was different from that of the naturally born group: the EPM test revealed reduced anxiety in the former. The results of the present study indicate that the rearing conditions as well as reproductive technologies affect some behavioral characteristics in adult ISIAH rats, although they develop arterial hypertension in all the conditions used in this study.